2016
DOI: 10.1111/jre.12410
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic characteristics of human gingival fibroblasts in response to oral bacteria

Abstract: The invasion of red-complex bacteria into gingival connective tissue can suppress the immune response of GFs and can be a source of persistent infection in connective tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
(79 reference statements)
0
17
0
2
Order By: Relevance
“…The other main gingival resident cells are GFs, which also participate in the immune response to oral bacteria by producing pro-inflammatory cytokines including IL-6 and IL-8 30 . In this study, we reported that IL-36s mRNA expression was not altered in human primary GFs infected with P. gingivalis .…”
Section: Discussionmentioning
confidence: 99%
“…The other main gingival resident cells are GFs, which also participate in the immune response to oral bacteria by producing pro-inflammatory cytokines including IL-6 and IL-8 30 . In this study, we reported that IL-36s mRNA expression was not altered in human primary GFs infected with P. gingivalis .…”
Section: Discussionmentioning
confidence: 99%
“…The data strongly argued that Leptotrichia may be crucially involved in the ‘fine-tune’ regulation of epithelial immune response to obtain homeostasis or propagate inflammatory response [48]. Jang et al [102] reported that L. wadei , Fusobacterium nucleatum , and Campylobacter gracilis when co-cultured with human gingival fibroblasts highly upregulated the expression of antimicrobial chemokine peptides and the proinflammatory mediators IL-6 and IL-8, whereas the red-complex bacteria stimulated low levels or often suppressed expression of these factors [102]. …”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
“…Leptorichias are opportunistic bacteria found in oral biofilm and saliva. Increased amounts of L. Wadei are associated to rheumatoid arthritis by stimulating the release of antimicrobial chemokines and proinflammatory mediators, IL-6 and IL-8 [15]. Despite non-significant, our analysis indicates an increase in IL-8 (2 folds) in CNr and IL-6 (1.8 folds) and MIP-α (6 folds) in MCI.…”
Section: Discussionmentioning
confidence: 70%